Comparing a thioglycosylated chlorin and phthalocyanine as potential theranostic agents. Issue 3 (1st February 2020) - Singh, Sunaina; Aggarwal, Amit; Bhupathiraju, N.V.S. Dinesh K.; Jovanovic, Ivana Radivojevic; Landress, Michael; Tuz, Michelle Paola; Gao, Ruomei; Drain, Charles M.
Graphical abstract: Abstract: Herein we describe the design, efficient synthesis, and photophysical properties of two macrocycle dyes for cancer theranostics. This study compares a glycosylated chlorin with a glycosylated phthalocyanine designed to specifically target cancer, wherein the photophysical properties enable both fluorescence imaging and the sensitization of the formation of reactive oxygen species (ROS) for photodynamic therapy. Both the compounds show low darktoxicity (IC50  > 100 μM). The glycosylated phthalocyanine showed low phototoxicity (IC50  > 100 μM) while glycosylated chlorin showed high phototoxicity (IC50  = 1–2 μM). ZnPcGlc8 has low solubility and also form aggregates in aqueous media, thus resulting in minimal uptake in two different human breast cancer cell lines: MDA-MB-231 and MCF-7. The glycosylated chlorin however was efficiently taken up by these two cell lines, thus allows fluorescence imaging in cells and in xenograft tumor model in mice. In this study, we find that the chlorin conjugate is the more promising theranostic agent.